Hyaline fibromatosis syndrome with a novel 4.41‐kb deletion in ANTXR2 gene: A case report and literature review - Yunqian Zhu; Xiaonan Du; Li Sun; Huijun Wang; Dahui Wang; Bingbing Wu (Molecular Genetics & Genomic Medicine, 2022)
Abstract Background Hyaline fibromatosis syndrome is a rare autosomal recessive disorder with ANTXR2 mutations characterised by the accumulation of hyaline substances in tissues. We present a case with the severe form—infantile systemic hyalinosis (ISH)—with long survival and review the literature. Methods and results Trio‐exome sequencing revealed compound heterozygous mutations, including a novel 4.41 kb deletion on 4q21.21 and the previously reported c.1294C > T mutation, in the ANTXR2 gene. He was diagnosed with ISH and treated symptomatically. After follow‐ups until 4 years of age, his recurrent respiratory infections and diarrhoea improved after one severe diarrhoea attack treated with intravenous gamma globulin. He is now awaiting surgical excision of gingival hypertrophy and joint contractures. Conclusion The novel gross deletion in ANTXR2 enriches the genetic mutation spectrum of hyaline fibromatosis syndrome. The manifestation of decreased foetal movement, acute‐infection attack or intravenous gamma globulin treatment may be associated with hyaline fibromatosis syndrome. A review of 116 reported cases reveals that missense mutations in the vWA domain are associated with joint symptoms, respiratory tract infection and diarrhoea, while frameshift mutations are associated with facial deformities and speech delays. We have enriched the current knowledge of the clinical manifestations and genetic mutation spectrum of HFS.